2023
DOI: 10.3390/v15102075
|View full text |Cite
|
Sign up to set email alerts
|

High Hepatitis E Virus (HEV) Seroprevalence and No Evidence of HEV Viraemia in Vietnamese Blood Donors

Le Chi Cao,
Vanessa Martin,
Le Thi Kieu Linh
et al.

Abstract: The prevalence of hepatitis E virus (HEV) in the Vietnamese population remains underestimated. The aim of the present study was to investigate the seroprevalence of HEV IgG/IgM antibodies and the presence of HEV RNA in blood donors as a part of epidemiological surveillance for transfusion-transmitted viruses. Serum samples from blood donors (n = 553) were analysed for markers of past (anti-HEV IgG) and recent/ongoing (anti-HEV IgM) HEV infections. In addition, all serum samples were subsequently tested for HEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, in some countries, where the virus is either endemic or non-endemic, HEV RNA was not detected in plasma samples from blood donors despite significant levels of seropositivity in the studied cohorts [ 27 , 28 ]. Indeed, differences in the frequency of detection of HEV viremia in donors can be explained by objective differences in the prevalence of HEV infection in the general population in a given territory.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some countries, where the virus is either endemic or non-endemic, HEV RNA was not detected in plasma samples from blood donors despite significant levels of seropositivity in the studied cohorts [ 27 , 28 ]. Indeed, differences in the frequency of detection of HEV viremia in donors can be explained by objective differences in the prevalence of HEV infection in the general population in a given territory.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveillance campaigns for HEV in animals and high-risk groups have been conducted in the Southern and Northern regions, revealing the circulation of genotypes 3 and 4 in domestic pigs [ 15 , 16 ]. Seroprevalence studies have reported HEV- IgG positivity ranging from 8% in pregnant women [ 11 ] to 27% in blood donors [ 17 ] and 53% in individuals exposed to pigs [ 18 ], highlighting a significant exposure in the Vietnamese population. Pigs comprised the largest proportion of livestock in Vietnam, accounting for 67% (23 million) in 2021 and 74% (25 million) in 2022 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%